(untitled) (International Journal of Engineering and Computer Science, 2015)
The cryogenic piping circuit is studied to design and to handle the Liquid hydrogen. It is one of the important piping circuit networks present in the fuel booster turbo pump which mainly comes under the cryogenic upper stage in Geo Synchronous Launch Vehicle of Indian Space Research Organisation at Mahendragiri.. It consists piping elements like expansion joints/loops with optimal placement of supports. This paper mainly discusses about the Thermal stresses induced in the piping circuits when liquid hydrogen flows through it and how these stresses can be reduced by incorporating various expansion loops. Cryogenic fluid servicing pipelines are tend to develop thermal stress due to contraction/ expansion of piping material during chilling/ warming from ambient to cryogenic temperature or vice versa. The present project is to design, analysis of cryogenic piping using Finite Element Method (FEM) tool and detailed engineering. Flexibility results can be determined by structural analysis by altering the elbow angles respectively.